The Application of Organic Semiconductor Materials in Spintronics - Zhang, Yixiao; Guo, Lidan; Zhu, Xiangwei; Sun, Xiangnan (Frontiers in Chemistry, 2020)
π-Conjugated semiconductors, primarily composed of elements with low atomic number, are regarded as promising spin-transport materials due to the weak spin-orbit coupling interaction and hence long spin relaxation time. Moreover, a large number of additional functions of organic semiconductors (OSCs), such as the abundant photo-electric properties, flexibility, tailorability, etc., endow the organic spintronic devices more unique properties and functionalities. Particularly, the integration of the photo-electric functionality and excellent spin transport property of OSCs in a single spintronic device has even shown the great potential for the realization of spin manipulation in OSCs. In this review, the application of OSCs in spintronic study will be succinctly discussed. As the most important and extensive application, the long-distance spin transport property of OSCs will be discussed firstly. Subsequently, several multifunctional spintronic devices based on OSCs will be summarized. After that, the organic-based magnet used for the electrodes of spintronic device will be introduced. Finally, according to the latest progress, spin manipulation in OSCs via novel spintronic device will be outlined, as well as other prospects and challenges.